2004
DOI: 10.3354/ame037305
|View full text |Cite
|
Sign up to set email alerts
|

A practical method for enumerating cysts of ciliates in natural marine sediments

Abstract: In order to determine the abundance of intact cysts of planktonic ciliates in natural sediments, we developed a new practical method using autofluorescence of the fixative glutaraldehyde. After treatment with glutaraldehyde, the cyst walls fluoresced yellowish-green under blue excitation. The fluorescence was always clear in the intact cysts, while only part of the empty cysts was weakly fluorescent. This fluorescence made detection of the intact cysts easy among detrital materials, even for the cysts covered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…There are no prior reports of the palynomorph here referred to as Palaeostomocystis sp.1, but its morphology closely resembles cysts of the ciliate Strombidium conicum as reported from modern marine sediments in Onagawa Bay (Ichinomiya et al, 2004). This species was found near the sub-arctic area of the western North Pacific at a shallow depth of 22 meters.…”
Section: (Paleo)environmental Significance Of Palaeostomocystissupporting
confidence: 49%
See 1 more Smart Citation
“…There are no prior reports of the palynomorph here referred to as Palaeostomocystis sp.1, but its morphology closely resembles cysts of the ciliate Strombidium conicum as reported from modern marine sediments in Onagawa Bay (Ichinomiya et al, 2004). This species was found near the sub-arctic area of the western North Pacific at a shallow depth of 22 meters.…”
Section: (Paleo)environmental Significance Of Palaeostomocystissupporting
confidence: 49%
“…Bujak (1984) classified the genus Beringiella, here treated as a taxonomic junior synonym of Palaeostomocystis, as having unknown affinity but possibly representing an egg capsule or an algal cyst. Ichinomiya et al (2004) reported cysts of the marine planktonic ciliate Strombidium conicum from modern marine sediments in Onagawa Bay near the subarctic area of the western North Pacific. Palaeostomocystis may also have biological affini-ties with heterotrophic cilates such as those that are abundant in the waters of central Greenland (Munk et al, 2003).…”
Section: Biological Affinity Of Palaeostomocystismentioning
confidence: 99%
“…of cysts kindly provided by A. Saage, University of Kiel, Germany; Ichinomiya et al. ), and tintinnids similar to F. arcuata (see below; Fenchel ; Margalef and Durán ; McManus and Katz ; Meunier ; Reid and John ; Van Breemen ). Cysts of hypotrichs, stichotrichs, and the halteriids Meseres Schewiakoff, 1892 and Halteria , however, lack a preformed emergence site; thus, the cyst is left through rupture of the wall (Foissner et al.…”
Section: Resultsmentioning
confidence: 99%
“…There are no prior reports of the palynomorph here referred to as Palaeostomocystis sp.l, but its morphology closely resembles cysts of the ciliate Strombidium conicum as reported from modern marine sediments in Onagawa Bay (Ichinomiya et al, 2004). This species was found near the sub-arctic area of the western North Pacific at a shallow depth of 22 meters.…”
Section: Of Palaeostomocystismentioning
confidence: 72%
“…without clear biological affinity. Ichinomiya et al (2004) reported cysts of the marine planktonic ciliate Strombidium conicum from modern marine sediments in Onagawa Bay near the subarctic area of the western North Pacific. These cysts closely resemble Palaeostomocystis sp.…”
Section: Biological Affinity Of Palaeostomocystismentioning
confidence: 98%